The Role of Skills in Islamic Financial Innovation: Evidence from Bahrain and Malaysia - Jessie Poon; Yew Wah Chow; Michael Ewers; Razli Ramli (Journal of Open Innovation: Technology, Market and Complexity, 2020)
A body of work has emerged that examines human capital from the perspective of skills to better understand the types of expertise that influence innovation. The relationship between skill and financial innovation, however, is poorly understood in the context of Islamic financial institutions (IFIs). IFIs are distinct from their conventional counterparts by their compliance with Shariah law. Based on a survey of IFIs in Bahrain and Malaysia, this paper examines the effect of different skills on IFI innovation. The findings indicate that while skill in Islamic finance positively influences innovation, skill in Shariah law does not. Cognitive-technical skill is also highly significant, but marketing skill has a negative effect. The results suggest that Islamic financial innovation relies on continuous improvement that sustains markets, product and service innovation. Sustaining innovation lends itself to abilities that are oriented towards problem solving and computation of Shariah and business risks. This favors skills of programming and expertise in Islamic finance over marketing and Shariah legal proficiency.